Widuri Dalam Berita Koran Belanda Akhir Abad XIX - Ilafi, Afiliasi; Larasaty, Larasaty (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2023)
Pemalang is one of regencies in Central Java Province. This region has a historical story that owned in every village. One of them is occurred in Widuri. Widuri has a feature from its famous folklore’s among society in Pemalang. Widuri village, now became Widuri urban village, also has a beautiful coast as one of family tourist destination in Pemalang and its surroundings. Despite of all, Widuri had an interesting story which is reported by Dutch newspapers during the dcolonial period. This writing is an investigationabout local history during the colonial period using a historiographic approach. News report from Dutch Newspaper used as a primary source for the main reference in this research. Furthermore, social and anthropological approaches used to reveal the continuity from colonial period to the present. The result reveal that Widuri has been chosen by Eurpeans as location for recreation and carrying out various social activities.